PROCESS PRODUCTION GRASS CUTTER BASED LITHIUM BATTERY - Abdul Rahman Agung Ramadhan (Asosiasi Dosen Muda Indonesia, 2022)
This battery-based lawn mower is a simple tool to cut grass efficiently and quickly without having to use gasoline and also without the need for an electric plug adapter to move the mower. The purpose of this paper is to be able to design a lawn mower, to know what components are used in the work process and also to know the working process of making a lawn mower. The main power source of this tool is from a series of 21 18650 series batteries with a capacity of 46 A which are connected in parallel and in series and combined with the BMS 3s module for protection and control of the system. With a large enough battery capacity, this tool is able to operate for approximately 45-60 minutes of use.